Fokal epilepsili hastalarda nöropsikolojik testler uygulayarak bilişsel işlev bozuklukları ve duygudurum değerlendirilmesi - Torun, Gülengül (My University, 2005)
Marmara Üniversitesi Tıp Fakültesi Nöroloji lepsi polikiliniğinde yürüttüğümüz bu çalışmada 94 fokal epilepsi hastası ve 20 sağlıklı kişiden oluşan kontrol grubuna nöropsikolojik testler uygulandı.Epilepsinin neden olduğu bilişsel işlev bozuklukları ve duygudurum bozuklukları araştırıldı. Saptanan bozuklukların hastaların yaşı,nöbet başlangıç yaşları,eğitim durumları,nöbetlerin süresi,son nöbet zamanı lezyon lateralizasyonu , lezyon lokalizasyonu ve ilaç kullanımı ile ilişkileri istatistiksel olarak incelendi Fokal epilepsi,bilişsel işlevler,depresyon,anksiyete,nöropsikolojik testler COGNITIVE DISFUNCTION AND MOOD DISORDERS ESTIMATED BY NEUROPSYCHOLOGICAL TESTS ON FOCAL EPILEPSY PATİENTS

This study has taken place in the epilepsy policlinic of the department of Neurology of the University of Marmara Medical Faculty.In this study neuro- psycological tests were applied to 94 focal epilepsy patients and20 healty control group patients .Cognitive function impairment and mood disorders caused by epilepsy has been searched.The relation between the detected disorders and the patients age,beginning age of seziure,patients educational state,duration of seziure,last seziure time ,lesion lateralisation,lesion localisation and drug therapy was statistically analyzed. Key words: Focal epilepsy,cognitive function,depression,anxiety,neuropsycological tests . .
Keywords: Nöroloji